How mobile app developers conceive of dyslexia and what it means for mobile app users - Kara Dawson; Pavlo Antonenko; Shilpa Sahay; Linda Lombardino (Interaction Design and Architecture(s), 2016)
This study surveys the landscape of 531 apps identified in a search for mobile apps for dyslexia and examines how their developers conceive of dyslexia. Results suggest most developers use the word dyslexia to increase the visibility of their apps within digital distribution platforms but do not intentionally design with dyslexics in mind. Those developers intentionally designing for dyslexics often have accurate but simplistic and one-dimensional conceptions of dyslexia and, unfortunately, some also have misconceptions especially as related to the myth that dyslexia can be cured or outgrown. Although a small number of developers are collaborating with dyslexia experts to design their apps, the onus for determining the quality of most apps is left to users. Examples of curated resource repositories and evaluation rubrics for mobile apps are provided to support users in this endeavor.